Biparietal diameter at 11–13 weeks' gestation in fetuses with open spina bifida. (22nd August 2013) - Khalil, A.; Coates, A.; Papageorghiou, A.; Bhide, A.; Thilaganathan, B.
ABSTRACT: Objective: To ascertain the reported association between reduced biparietal diameter (BPD) at 11–13 weeks' gestation and open spina bifida and to investigate its predictive value in a single‐center study. Methods: This was a retrospective study of fetuses in which BPD was measured at 11–13 weeks' gestation, including 27 fetuses with isolated open spina bifida subsequently diagnosed at 16–24 weeks and 7775 unaffected controls. BPD values were converted into multiples of the expected median (MoM) after adjustment for crown–rump length and maternal characteristics. Multivariable logistic regression analysis was used to determine the maternal characteristics significantly associated with spina bifida. The performance of screening was determined by receiver–operating characteristics curve analysis. BPD values at 11–13 weeks' gestation were compared with those measured in the second trimester using Z‐scores. Results: BPD values at 11–13 weeks' gestation were below the 5 th centile in 44.4% of cases of open spina bifida. In these fetuses, the median BPD MoM value was significantly smaller than that in the control group (0.930 vs 0.998 MoM; P < 0.0001). Multivariable logistic regression analysis showed a significant contribution from maternal age ( P = 0.008) and BMI ( P = 0.028) to the association between BPD MoM and spina bifida. The detection rate using BPD measurements in the first trimester was 55.6% with a false‐positive rate of 11.6%. In fetuses with open spina bifida, the BPD Z ‐scores were significantly lower at 16–24 weeks compared to those recorded at 11–13 weeks (median, –1.71 (range, –3.98 to –0.20) vs –1.30 (–3.75 to 2.61); P = 0.006). Conclusion: Fetuses with open spina bifida have a smaller BPD in the first trimester. This observation may be useful in early screening. It is likely that a combination of maternal characteristics such as age and BMI, fetal BPD and maternal serum alpha‐fetoprotein measured in the first trimester would provide a clinically useful screening test for open spina bifida. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.